Economic analysis of Eucalyptus biomass cultivation for energy in Argentina - Olemberg, Demián Jeremías (2024)
The objective of this study was to conduct an ex-ante evaluation of the viability of Eucalyptus grandis biomass plantations in northeastern Argentina, modeling the effects of changes in the economic context (relative prices) for the years 2010–2022. The developed model enables the estimation of the minimum viable price for forest biomass production and includes a sensitivity analysis. Moreover, it contributes to understanding the evolution of economic viability conditions, enabling anticipation of future scenarios. The results indicate that, for most of the time series analyzed and under average conditions for different scenarios, the model is not viable. This is because the minimum price set by biomass production and supply conditions exceeds the maximum price that the energy transformation stage can pay without incurring losses. Our methodology could assist in modelling future economic investment projects, and facilitate the incorporation of technical, economic and policy variants. The results establish a baseline on which future project evaluations could more explicitly incorporate environmental aspects and other externalities in decision-making from a societal standpoint.